Lactose-reduced infant formula with added corn syrup solids is associated with a distinct gut microbiota in Hispanic infants. Issue 1 (9th November 2020) - Jones, Roshonda B.; Berger, Paige K.; Plows, Jasmine F.; Alderete, Tanya L.; Millstein, Joshua; Fogel, Jennifer; Iablokov, Stanislav N.; Rodionov, Dmitry A.; Osterman, Andrei L.; Bode, Lars; Goran, Michael I.
ABSTRACT: Infant formula feeding, compared with human milk, has been associated with development of a distinct infant gut microbiome, but no previous study has examined effects of formula with added sugars. This work examined differences in gut microbiota among 91 Hispanic infants who consumed human milk [at breast (BB) vs. pumped in bottle (BP)] and 2 kinds of infant formula [(traditional lactose-based (TF) vs. lactose-reduced with added sugar (ASF)]. At 1 and 6 months, infant stool was collected to characterize gut microbiota. At 6 months, mothers completed 24-hour dietary recalls and questionnaires to determine infant consumption of human milk (BB vs. BP) or formula (TF vs. ASF). Linear regression models were used to determine associations of milk consumption type and microbial features at 6 months. Infants in the formula groups exhibited a significantly more 'mature' microbiome than infants in the human milk groups with the most pronounced differences observed between the ASF vs. BB groups. In the ASF group, we observed reduced log-normalized abundance of Bifidobacteriaceae (TF-BB Mean Difference = −0.71, ASF-BB Mean Difference = −1.10), and increased abundance of Lachnospiraceae (TF-BB Mean Difference = +0.89, ASF-BB Mean Difference = +1.20). We also observed a higher Community Phenotype Index of propionate, most likely produced by Lachnospiraceae, in the ASF group (TF-BB Mean Difference = +0.27, ASF-BB Mean Difference = +0.36). This study provides the first evidence that consumption of infant formula with added sugar may have a stronger association than birth delivery mode, infant caloric intake, and maternal BMI on the infant's microbiome at 6 months of age.